2017
DOI: 10.4172/2329-6836.1000282
|View full text |Cite
|
Sign up to set email alerts
|

Gallium (III)-Metalloporphyrin Grafted Magnetite Nanoparticles for Fluoride Removal from Aqueous Solutions

Abstract: Fluoride is a critical micronutrient for human health and is usually ingested through food and drinking water. This technique has done in monitoring the concentration of fluoride in water complications at mining operation that it effects on the environment. Fe 3 O 4 nanoparticles were synthesized by coprecipitation of Fe 2+ and Fe 3+ in an alkaline solution, their surface was then modified with 3-aminopropyltriethoxysilane and a Ga(III) porphyrin complex, Ga(TCPP)Cl 2 [TCPP: tetrakis (4-carboxyphenyl) porphyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…They further used this bimetallic magnetic composite nano adsorbent (Fe 3 O 4 @Fe-Ti) in a fluidized bed system for fluoride removal. 17 Asgari et al, 18 synthesized Fe 3 O 4 magnetic nanoparticles and modified the surface with 3-aminopropyltriethoxysilane and a Ga (III) porphyrin complex, Ga (TCPP) Cl 2 [TCPP: tetrakis (4carboxyphenyl) porphyrin]. They tested the sample for fluoride adsorption and found that fluoride with an initial concentration of 10 mg/L was reduced to 0.3mg/L in contact time of 30 minutes.…”
Section: Magnetic Nanoparticles For Fluoride Removalmentioning
confidence: 99%
“…They further used this bimetallic magnetic composite nano adsorbent (Fe 3 O 4 @Fe-Ti) in a fluidized bed system for fluoride removal. 17 Asgari et al, 18 synthesized Fe 3 O 4 magnetic nanoparticles and modified the surface with 3-aminopropyltriethoxysilane and a Ga (III) porphyrin complex, Ga (TCPP) Cl 2 [TCPP: tetrakis (4carboxyphenyl) porphyrin]. They tested the sample for fluoride adsorption and found that fluoride with an initial concentration of 10 mg/L was reduced to 0.3mg/L in contact time of 30 minutes.…”
Section: Magnetic Nanoparticles For Fluoride Removalmentioning
confidence: 99%
“…Therefore, the evaluation of genetic variability may be key to improving jojoba yield and properties in the near future [16]. Several studies have beenreported on cultivated Egyptian jojoba shrubs [17][18][19][20][21], however, few have investigated the chemical properties of JO and its chemical composition.…”
Section: Introductionmentioning
confidence: 99%